2005
DOI: 10.1002/pmic.200400925
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of bovine skeletal muscle hypertrophy

Abstract: Myostatin plays a major role in muscle growth and development and animals with disruption of this gene display marked increases in muscle mass. Little is known about muscle physiological adaptations in relation to this muscle hypertrophy. To provide a more comprehensive view, we analyzed bovine muscles from control, heterozygote and homozygote young Belgian blue bulls for myostatin deletion, which results in a normal level of inactive myostatin. Heterozygote and homozygote animals were characterized by a highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
100
0
7

Year Published

2005
2005
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 145 publications
(124 citation statements)
references
References 49 publications
17
100
0
7
Order By: Relevance
“…Signatures related to muscle energy metabolism and growth As expected (Bouley et al, 2005;Cassar-Malek et al, 2007;Chelh et al, 2009b), our results revealed additional evidences of glycolytic shift within skeletal muscle in the absence of functional MSTN with increased abundance of fast-twitch proteins (e.g. H-MyBP and PGM1) and decreased abundance of H-FABP in DM muscles.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Signatures related to muscle energy metabolism and growth As expected (Bouley et al, 2005;Cassar-Malek et al, 2007;Chelh et al, 2009b), our results revealed additional evidences of glycolytic shift within skeletal muscle in the absence of functional MSTN with increased abundance of fast-twitch proteins (e.g. H-MyBP and PGM1) and decreased abundance of H-FABP in DM muscles.…”
Section: Discussionsupporting
confidence: 76%
“…In the absence of functional MSTN, we showed a differential expression of genes and proteins related to the muscle energy metabolism (Bouley et al, 2005;Cassar-Malek et al, 2007), extracellular-matrix (Cassar-Malek et al, 2007, and cell survival/anti-apoptotic pathway (Cassar-Malek et al, 2007;Chelh et al, 2009b). Activation of the PI3K/Akt pathway (Chelh et al, 2009b) and of anti-apoptotic processes (Chelh et al, 2009a) represents new potential mechanisms to account for muscle hypertrophy as these processes are crucial determinants for muscle protein biosynthesis.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…In addition, double-muscled compared with conventional cattle and Charolais selected for high v. low muscle growth capacity have muscles with a higher proportion of fast glycolytic fibres (Cassar-Malek et al, 2005;Picard et al, 2006) and a lower intramuscular fat content (Gotoh et al, 2009), as observed Interaction between adipose tissue and muscle between genotypes with a high v. low lean-to-fat ratio (May et al, 1994;Bellmann et al, 2004). This is accompanied by a reduced expression of proteins related to oxidative and lipid metabolism in muscle (Bouley et al, 2005;Wang et al, 2005;Bonnet et al, 2007;Jurie et al, 2007;Graugnard et al, 2009). In several studies comparing pure or crossbred Pirenaican, Limousin, Holstein, Wagyu, Santa Gertrudis, Angus, and Japanese Black growing cattle it was repeatedly observed that the leaner breeds had lower adipocyte size in carcass and muscular WAT (Miller et al, 1991;May et al, 1994;Eguinoa et al, 2003), concomitant with lower gene expression of C/EBPs (Yamada et al, 2009) and PPARg (Bonnet et al, 2007), lipogenic activities (Hood and Allen, 1973;Miller et al, 1991;Eguinoa et al, 2003;Bonnet et al, 2007), leptin gene expression (Chilliard et al, 2005;Bonnet et al, 2007), and higher resistin (Komatsu et al, 2005) when slaughtered at similar age.…”
Section: Nutritional and Physiological Control Of Muscular And At Growthmentioning
confidence: 99%
“…The use of both micro-array and proteomic analyses showed a clear fibre phenotype switch in Mst-null muscles from slow to fast-twitch fibres (Bouley et al, 2006;Steelman et al, 2006) (see section IGF-1, b 2 -agonist and myostatin-null signal fast fibre phenotype). Mst has been recently found to promote adipogenesis in C3H 10T(1/2) cells which appears to be associated with adipocyte lineage commitment (Artaza et al, 2005).…”
Section: Fibre Number: Mediators Of Muscle Hyperplasiamentioning
confidence: 99%